Ethics of safety reporting of a clinical trial - Amrita Sil; Nilay Kanti Das (Wolters Kluwer Medknow Publications, 2017)
Clinical trial related injury and serious adverse events (SAE) are a major area of concern. In all such scenarios the investigator is responsible for medical care of the trial participant and also ethically bound to report the event to all the stakeholders of the clinical trial. The trial sponsor is responsible for ongoing safety evaluation of the investigational product, reporting and compensating the participant in case of any SAE. The Ethics Committee and regulatory body of the country are to uphold the ethical principles of beneficence, justice, non-maleficence in such cases. Any unwanted and noxious effect of a drug when used in recommended doses is an adverse drug reaction (ADR) whereas if causal association is not yet established it is termed adverse event (AE). An AE or ADR that is associated with death, in-patient hospitalization, prolongation of hospitalization, persistent or significant disability or incapacity, a congenital anomaly, or is otherwise life threatening is termed as an SAE. The principal investigator reports the event to the licensing authority (DCGI), sponsor and Chairperson of the Ethics Committee (EC) within 24 hours of occurrence of the SAE. This report is furthered by a detailed report by both the investigator and the EC and given to the DCGI who then gives a final decision on the amount of compensation to be given by the sponsor or the sponsor's representative to the grieving party.